Pengaruh IKIGAI Guru BK dan Iklim Kerja di Sekolah Terhadap Kinerja Guru BK - Leni Murni Hayati; Firman Firman; A Muri Yusuf (INDONESIAN COUNSELING AND PSYCHOLOGY, 2021)
The purpose of this study was to examine the effect of Counselor Ikigai and the Teacher Counseling's work climate on the performance of Teacher Counselings. This type of research used a descriptive method with a quantitative approach. This study also uses the regression method which aims to examine the effect/value of the influence of two independent variables on one dependent variable. The research population is all Teacher Counselings in South Solok Regency. A sample of 39 respondents was Teacher Counselings. The results of data analysis and hypothesis testing indicate that the three hypotheses tested in this study are acceptable. The results show that Ikigai and work climate together can explain the performance of Teacher Counselings at SMA Solok Selatan Regency